2020
DOI: 10.1002/srin.201900591
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Crystallographic Texture, and Stretch‐Flangeability of Hot‐Rolled Multiphase Steel

Abstract: The microstructure, crystallographic texture, strain hardening in the hole edge‐punched and stretch‐flangeability of hot‐rolled multiphase sheet steel is investigated by scanning electron microscopy, electron backscatter diffraction, and microhardness measurements. The results show that the strain hardening in the hole edge‐punched is not the main factor that influences the hole expansion ratio. The bainite fraction, average grain area, and kernel average misorientation distribution mean are microstructure fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Reference [15] used Equation (7), and it was also applied in this study, although the equation does not include the main carbide forming elements (Ti, Mo, V, and Nb). This study also adopted the assumptions concerning the carbon and nitrogen content made in ref.…”
Section: Contribution Of Strengthening Mechanisms To Ysmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [15] used Equation (7), and it was also applied in this study, although the equation does not include the main carbide forming elements (Ti, Mo, V, and Nb). This study also adopted the assumptions concerning the carbon and nitrogen content made in ref.…”
Section: Contribution Of Strengthening Mechanisms To Ysmentioning
confidence: 99%
“…[1][2][3][4] The relatively high-volume fraction of martensite and/or bainite, which is often required to achieve a high TS value in the steel, unfortunately tends to have an adverse effect on the stretch flangeability of the dual-phase (DP), multiphase (MP), and low-alloyed, transformation-induced plasticity (TRIP) steels. [6][7][8][9][10][11][12] Excellent strength and flangeability properties can be achieved in the complex-phase (CP) steels and in a steel consisting of tempered martensite and granular bainite; however, that required a strict thermomechanical process control together with a well-balanced steel chemistry. [2,13] Besides the abovementioned steels, the fully ferritic steel grades typically have excellent formability but a relatively low strength; thus, Funakawa et al [14] introduced a method to increase their strength substantially by nanometer-sized interphase precipitates (IP) that were formed during the austenite-to-ferrite phase transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The radial and circumferential stresses on the right-hand side of Equation (26) should be eliminated using Equations (15) and 16, on the right-hand side of Equation (27) using Equations (18) and (19). The solutions (26) and (27) are valid if the respective yield criterion is not violated in the range a ≤ ρ ≤ 1. This condition is represented as…”
Section: Of 16mentioning
confidence: 99%
“…The authors of [25] studied the influence of continuous annealing temperature on battery shell steel's mechanical properties. In [26], the normal anisotropy of crystallographic orientations has been calculated to evaluate the effect of crystallographic texture on the stretch-flangeability during the hole expansion test of hot-rolled multiphase steel.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research showed that a lower strength differential between the phases, by tempering heat treatment [7] or by adding some alloying elements like Nb [8], could increase the hole expansion ratio (HER). Furthermore, lowering martensite content [9], smaller grain size [10], and more homogeneous microstructure [11] can improve HER. These microstructure changes can vary the damage behavior and mechanism in DP steel as well.…”
Section: Introductionmentioning
confidence: 99%